(untitled) (Bangladesh Heart Journal, 2017)
Background: Coronary heart disease is a major cause of death and is a global health problem and reaching epidemic in both developed and as well as in developing countries. In patients with acute myocardial infarction baroreceptor mediated hormonal activation has a prognostic value. Clinical importance of hyponatraemia in ST-elevation acute myocardial infarction has not been fully understood. Hyponatremia which developed in early phase of AMI has been recently advocated as an important prognostic factor in several studies. Objectives: The aim of the study was to investigate the impact of hyponatremia on in-hospital outcomes in patients with ST-elevation acute myocardial Infarction treated by thrombolysis. Methods: Hyponartaemia was defined as a sodium concentration <135 mmol/L. Hyponatremia which developed at 72 hours after admission was defined as early developed hyponatraemia. This study is a prospective observational study. A purposive sampling technique was used to select the sample. In this study data on 100 patients with ST-elevation acute myocardial infarction were analyzed. This study was done in the department of Cardiology Mymensingh Medical College Hospital from July 2014 to June 2015. Patients admitted in the department of Cardiology MMCH with acute STelevation myocardial infarction and treated with thrombolysis were evaluated for serum sodium level at admission and at 72 hours after admission. Total 100 patients were studied. Fifty patients with hyponatraemia were Group-I and fifty patients with normal sodium level were Group-II. Then the in-hospital outcome variables were analyzed. Results: Among the study population 85% were male and 15% were female. Age range was 25 years to 74 years. Mean age was 52.88±11.88. Risk factors such as smoking, hypertension, diabetes mellitus, dyslipidemia and F/H of CAD were evaluated. Highest percentage of study population had hypertension (52%) followed by dyslipidemia (49%), smoker (46%), diabetes mellitus (39%) and F/H of CAD had (24%) of study population. There were five outcome variables such as heart failure, cardiogenic shock, arrhythmia, duration of hospital stay and death. Total 12 patients died. 10 patients died in Group-I and 2 patients died in Group-II. Among the outcome variables death, heart failure and hospital stay was more in Group-I and was statistically significant. Conclusion: Early developed hyponatremia in patients with ST-elevation acute myocardial infarction was an independent predictor of prognosis. Heart failure, duration of hospital stay and death was more in hyponatraemic patients and Prognosis worsen with increasing severity of hyponatremia. Plasma sodium level may serve as a simple marker to identify patient at high risk. Bangladesh Heart Journal 2017; 32(1) : 29-35